Imidazoporphyrins with appended polycyclic aromatic hydrocarbons: To conjugate or not to conjugate?. (February 2021) - Birin, Kirill P.; Abdulaeva, Inna A.; Polivanovskaia, Daria A.; Martynov, Alexander G.; Shokurov, Alexander V.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu
Abstract: Herein we report the synthesis and characterization of a series of new dyads – imidazo-fused Ni(II) porphyrinates, containing polycyclic aromatic hydrocarbons (PAH) at the C-2 position of the imidazole ring, including pyrene – 1Pyr, anthracene – 1An, and diphenylanthracene – 1Ph 2 An . Electronic communication between the tetrapyrrolic macrocycles and PAH moieties was comprehensively studied by UV–Vis and fluorescence spectra together with quantum-chemical modelling. DFT calculations, including geometry optimization and analysis of the frontier orbitals, has revealed the efficient conjugation of pyrene and anthracene with porphyrin π-system, while 1Ph 2 An dyad possessed two isolated non-conjugated π-systems. Interestingly, these conclusions could not be unambiguously ruled out of UV–Vis spectroscopy data alone. Finally, the presence or absence of conjugation was confirmed using the analysis of ellipticities of bond critical points, thus proving this method to be a convenient tool to study the conjugation in multichromophoric porphyrin-based systems. Highlights: New porphyrin/polyaromatic hydrocarbon dyads. Quantum-chemical rationalization of the electronic communication. Tuning of the degree of conjugation.